The Diagnosis and Treatment of Age-Related Macular Degeneration - Stahl, Andreas (Deutsches Ärzteblatt international, 2020)
Age-related macular degeneration (AMD) is thought to cause approximately 9% of all cases of blindness worldwide. In Germany, half of all cases of blindness and high-grade visual impairment are due to AMD. In this review, the main risk factors, clinical manifestations, and treatments of this disease are presented. This review is based on pertinent publications retrieved by a selective search in PubMed for original articles and reviews, as well as on current position statements by the relevant specialty societies. AMD is subdivided into early, intermediate, and late stages. The early stage is often asymptomatic; patients in the other two stages often have distorted vision or central visual field defects. The main risk factors are age, genetic predisposition, and nicotine consumption. The number of persons with early AMD in Germany rose from 5.7 million in 2002 to ca. 7 million in 2017. Late AMD is subdivided into the dry late form of the disease, for which there is no treatment at present, and the exudative late form, which can be treated with the intravitreal injection of VEGF inhibitors. More research is needed on the dry late form of AMD in particular, which is currently untreatable. The treatment of the exudative late form with VEGF inhibitors is labor-intensive and requires a close collaboration of the patient, the ophthalmologist, and the primary care physician.